Informing the future : critical issues in health. - Institute of Medicine (U.S.) (Washington, D.C. : Institute of Medicine of the National Academies, 2003)
The Institute of Medicine: Adviser to the Nation -- Highlighted reports -- Global health and infectious disease -- Health sciences and the research enterprise -- Ensuring food safety and proper nutrition -- Assuring the public's health -- Health care delivery system and performance capabilities -- Human security and bioterrorism -- Military personnel and veterans -- Robert Wood Johnson Health Policy Fellowships Program -- Senior nurse scholar program -- Recent and upcoming reports.
The Institute of Medicine: adviser to the nation -- Highlighted reports -- Global health and infectious disease -- Health sciences and the research enterprise -- Ensuring food safety and proper nutrition -- Assuring the public's health -- Health care delivery system and performance capabilities -- Human security and bioterrorism -- Military personnel and veterans -- Robert Wood Johnson Health Policy Fellowships Program -- Senior nurse scholar program -- Recent and upcoming reports.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Health planning -- United States; Public health -- United States; Medical care -- United States; Health planning; Public health; Health Planning; Public Health; Delivery of Health Care -- trends; Health Services Needs and Demand -- trends; Health Services Needs and Demands -- trends; United States; Santé publique -- Planification -- États-Unis.; Santé publique -- États-Unis.; Santé publique -- Planification; Santé publique; public health; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Health planning; Medical care; Public health; United States; Electronic texts